2021
DOI: 10.3390/v13081662
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Genus Human Papillomavirus 8 E6 Destabilizes the Host Genome by Promoting p300 Degradation

Abstract: The beta genus of human papillomaviruses infects cutaneous keratinocytes. Their replication depends on actively proliferating cells and, thus, they conflict with the cellular response to the DNA damage frequently encountered by these cells. This review focus on one of these viruses (HPV8) that counters the cellular response to damaged DNA and mitotic errors by expressing a protein (HPV8 E6) that destabilizes a histone acetyltransferase, p300. The loss of p300 results in broad dysregulation of cell signaling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 136 publications
(191 reference statements)
0
6
0
Order By: Relevance
“…Resulting hyperproliferative epithelium can form papillomas and represents a resource of new virus progeny. 21 In conjunction with chronic UV-exposure, however, cutaneous PVs interfere with DNA repair, 54,55 favoring the accumulation of driver mutations, for example, in the p53 gene, 14 that apparently results in both favoring the outgrowth of cells with a pathophysiological network counterselective for viral replication and making viral gene expression dispensable (Figures 2A and 3B).…”
Section: Discussionmentioning
confidence: 99%
“…Resulting hyperproliferative epithelium can form papillomas and represents a resource of new virus progeny. 21 In conjunction with chronic UV-exposure, however, cutaneous PVs interfere with DNA repair, 54,55 favoring the accumulation of driver mutations, for example, in the p53 gene, 14 that apparently results in both favoring the outgrowth of cells with a pathophysiological network counterselective for viral replication and making viral gene expression dispensable (Figures 2A and 3B).…”
Section: Discussionmentioning
confidence: 99%
“…The interference with UV damage repair by HPV5 and HPV8 E6 causes a more frequent collapse of replication forks into mutagenic DSBs. Erroneous DSB repair can cause the loss of large regions of DNA, chromosome translocation/rearrangements, and aneuploidy [ 67 , 68 ]. Two major pathways, homologous recombination (HR) and non-homologous end-joining (NHEJ) have evolved to repair DSBs with high fidelity.…”
Section: Beta Hpv and Genomic Instabilitymentioning
confidence: 99%
“…Inhibition of TGF-β and NOTCH signaling by E6 inhibits differentiation of squamous epithelial cells [ 98 , 99 , 101 , 105 ]. Additionally, the cutaneous HPV E6 proteins also thwart the DNA damage response and increase the susceptibility of the infected cells to UV-induced DNA damage at least in part through interactions with the p300 protein [ 106 , 107 , 108 , 109 ]. While cutaneous HPV E6 proteins do not detectably interact with E6AP and thus do not target p53 for degradation, a study that investigated the effects of β-HPV E6 proteins on p53 reported that a subset of cutaneous HPV E6 proteins may inhibit activation of p53 by DNA damage [ 110 ].…”
Section: Biological Activities Of E6 and E7 Proteins Encoded By Cutan...mentioning
confidence: 99%